Assessment of trec and krec levels in COVID-19 patients with varying disease severity - M. A. Saitgalina; Yulia V. Ostankova; Natalia A. Arsentieva; Zoya R. Korobova; Natalia E. Liubimova; Victor A. Kashchenko; Alexandr N. Kulikov; Dmitry E. Pevtsov; Oksana V. Stanevich; Ekaterina I. Chernykh; Areg A. Totolian (Инфекция и иммунитет, 2023)
According to the WHO data, the number of infected people exceeded 765.2 million people during the COVID-19 pandemic. The severity of patient’s condition is determined by immune system hyperactivation. Activation of T- and B-lymphocyte subsets plays a prominent role in the control of infectious process. A content of small circular DNA molecules — T-cell receptor excision circles (TREC — T-cell receptor excision circles) and B-cell (“kappa”) excision rings (KREC — Kappa-deleting recombination excision circles) — in the peripheral blood can be used as a marker of the functionally active T and B cells maturation. The purpose of this work is to quantify peripheral blood TREC and KREC level in patients with the new coronavirus infection COVID-19 of varying severity.Materials and methods.The material consisted of 1028 blood samples from patients with a confirmed diagnosis of COVID-19, as well as 717 blood samples from apparently healthy volunteers. The content of TREC and KREC DNA fragments in the total DNA fraction was assessed by quantitative Real-time PCR using the “TREC/KREC-AMP PS” test system (St. Petersburg Pasteur Institute, Russia). Blood cell phenotyping was carried out using flow cytometry.Results.TREC/KREC levels were significantly reduced in COVID-19 patients (p 0.0001 at 95% CI). A significant direct correlation was established between the levels of peripheral blood TREC molecules and level of CD45+CD3+CD19–T cells (r = 0.59, p 0.0001), as well as between KREC level and count of CD45+CD3–CD19+B cells (r = 0.66, p 0.0001). The level of TREC molecules in patients with severe vs. moderate infection was significantly reduced in patients aged 30–39 years old (p = 0.0404) and 40–49 years old (p = 0.0356). The negative correlation between severity of COVID-19 clinical manifestations and TREC level in the blood of patients in 30–49 year age group indicates about an opportunity of using this analyte as a diagnostic and prognostic laboratory marker of patient’s condition. A simple PCR analysis algorithm makes it relevant to use the described method for assessing a state of immunity in coronavirus patients in the context of systemic negative impact of the SARS-CoV-2 virus on human organism.